ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE PADA WEBSITE LEMBAGA PERLINDUNGAN PEREMPUAN DAN ANAK (LPPA) MENGGUNAKAN METODE DESIGN THINKING DAN HEURISTIC EVALUATION - Vanka Putriana Ariningtiyas (2024)
The Institute for the Protection of Women and Children (LPPA) is an institution that is active in the protection of women's and children's rights. The LPPA is also consensual in providing legal support both at the police level and at the court level. Research is being done to improve usability and develop the LPPA website to become more known to the general public. This study uses the heuristic evaluation method, where the testers themselves are experts in usability, UI, and UX. The evaluators will later use a measure of severity ratings. There is a problem outcome where the total is specific: its indicator H2: Match Between System and The Real World with 9 problems that have a SR ratio of 2.33; H4: Consistency and Standards with 13 issues that have an SR ratio of 2.61; H7: Flexibility and Efficiency of Use with 5 problems with an SR ratio of 2.8; and H8: Aesthetic and Minimalist Design with the highest problem of 22 with a SR rating of 2.59. The result of the problem is processed by the researchers, who will subsequently give a re-design display using the Design Thinking method in the form of a prototype for the recommendation of an improvement display on the official LPPA website to the LPPA.